Value of computed tomography-defined visceral fat area as a risk factor for endometrial cancer - Jae-hyun Cho; Jeong Sig Kim; Suyeon Park; Woo Young Kim (Clinical and Experimental Obstetrics & Gynecology)
Objective: Obesity is a risk factor for endometrial cancer. Recently, visceral fat is strongly associated with obesity-related carcinogenesis, more than subcutaneous fat. In this study, we hypothesized that the visceral fat measured by computed tomography (CT) contributes to the occurrence of endometrial cancer. Methods: A retrospective chart review of patients undergoing primary surgery for endometrial cancer was conducted. The volume of visceral fat was measured by CT scans performed at the fourth lumbar level for all participants. Body fat distributions assessed by a direct method in 52 endometrial cancer cases were compared with those of age- and BMI-matched healthy community controls. Results: Case group showed significantly higher mean visceral fat area (VFA; 76.2 ± 25.0 vs. 62.2 ± 13.9 cm2, P = 0.007). The mean total fat area (TFA; 270.3 ± 99.9 vs. 238.9 ± 53.8 cm2, P = 0.137) and subcutaneous fat area (SFA; 194.2 ± 86.5 vs. 176.7 ± 45.8 cm2, P = 0.315), however, presents no significant differences. VFA showed lower correlation with BMI (r2 = 0.299, P < 0.001) than to SFA (r2 = 0.528, P < 0.001) or TFA (r2 = 0.584, P < 0.001). In receiver operator characteristic (ROC) curve, at a VFA value of 70.8 cm2, sensitivity and specificity of the case group was 55.8% and 75%, respectively. Conclusion: Increased abdominal visceral fat is associated with endometrial cancer risk and can be predicted by measuring CT scans. Furthermore, as the most independent factor of BMI, VFA may provide additional information for representative risks of endometrial cancer.